Rangeland Biophysical Resource Assessment in Southern Ethiopia: Baseline Study Report - Eba, Bedasa; Ebro, Abule; Sircely, Jason A.; Ijo, A.; Tilahun, M. (International Livestock Research Institute, 2024)
The International Livestock Research Institute (ILRI), in partnership with African Medical and Research Foundation (Amref) and Veterinaires Sans Frontiere (VSF) Suisse, are jointly implementing HEAL (One Health for Humans, Environment, Animals and Livelihood in parts of Kenya, Ethiopia and Somalia. ILRI is implementing the rangeland health component. Between December 2022 and January 2023, a baseline rangeland biophysical assessment was undertaken in Moyale and Filtu districts of the Somali Region and Moyale District of Borana Zone of Oromia Region in Ethiopia at 12 monitoring locations in four rangeland units: Wayama, Osobey-Golba, Dukusu and Arda Olla.